Kajian Geometri Jalan Tambang Terhadap Produksi Pengangkutan Batu Andesit pada PT Silva Andia Utama di Kecamatan Batujajar, Kabupaten Bandung Barat, Provinsi Jawa Barat - Rama Aditya; Zaenal; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Silva Andia Utama is an andesite mining company located in Giriasih Village, Batujajar District, West Bandung Regency, West Java Province. The failure to achieve the production target of 15,292.8 BCM/month is a problem for this company, where one of the factors is the non-standard road geometry, such as narrow road widths which result in the means of conveyance not working optimally, thus affecting the cycle time of the equipment. From these problems, it is necessary to improve the geometry of the mine road to maximize the speed of the conveyance, so that the conveyance cycle time decreases and production increases. This study discusses the influence of mining road geometry on increasing productivity based on AASHTO (American Association of State Highway and Transportation Officials) and Ministerial Decree No. 1827/K/30/MEM/2018, which concerns road geometry including straight road width, bend condition road width, grade, bend radius, cross slope, superelevation, and actual Rimpull calculations . In this mine road geometry study, it is then linked to the production of digging-loading and hauling equipment to increase mining production of andesite. The results of this study obtain production in actual conditions of 13.534,5 BCM/month. The actual calculation results for this production have not reached the production target, so one of the factors in increasing production is the need to improve the geometry of mine roads that do not meet AASHTO (American Association of State Highway and Transportation Officials) standards and Ministerial Decree No.1827/K/30/MEM/2018. In the actual mining road geometry conditions, the average straight road width is 8.25 meters and for the bend condition road width is an average of 7.27 meters. On the slope of the road (grade) obtained a value of 0% - 21.22% in theoritical conditions. After repairing the geometry of mine road the production value of the conveyance of 16,929,12 BCM/month. With this value, production will increase, so that the production target desired by the company is achieved. Keywords: AASHTO, Cycle Time, Road Geometry, Production. Abstrak. PT Silva Andia Utama merupakan salah satu perusahaan penambangan batu andesit yang terletak di Desa Giriasih, Kecamatan Batujajar, Kabupaten Bandung Barat, Provinsi Jawa Barat. Tidak tercapainya target produksi sebesar 15.292,8 BCM/bulan menjadi permasalahan di perusahaan ini, dimana salah satu faktornya adalah geometri jalan yang tidak sesuai standar, seperti lebar jalan yang sempit mengakibatkan alat angkut tidak bekerja secara optimal, sehingga berpengaruh terhadap waktu edar alat tersebut. Dari permasalahan tersebut, maka perlu dilakukannya perbaikan geometri jalan tambang untuk memaksimalkan kecepatan pada alat angkut, sehingga waktu edar alat angkut turun dan produksi meningkat. Penelitian ini membahas mengenai pengaruh geometri jalan tambang terhadap peningkatan produktivitas berdasarkan AASHTO (American Association of State Highway and Transportation Officials) dan Kepmen No. 1827/K/30/MEM/2018, yaitu mengenai geometri jalan meliputi lebar jalan kondisi lurus, lebar jalan kondisi tikungan, kemiringan jalan (grade), jari-jari tikungan, kemiringan melintang (cross slope), dan superelevasi secara aktual. Pada kajian geometri jalan tambang ini, kemudian dikaitkan dengan produksi alat gali-muat dan angkut untuk meningkatkan produksi penambangan batu andesit. Hasil penelitian ini mendapatkan produksi dalam keadaan aktual sebesar 13.534,5 BCM/bulan. Hasil perhitungan secara aktual pada produksi tersebut belum mencapai target produksi, sehingga salah satu faktor dalam meningkatkan produksi perlu dilakukan perbaikan geometri jalan tambang yang belum memenuhi standar AASHTO (American Association of State Highway and Transportation Officials) dan Kepmen No. 1827/K/30/MEM/2018. Pada kondisi aktual geometri jalan tambang untuk lebar jalan kondisi lurus rata-rata 8,25 meter dan untuk lebar jalan kondisi tikungan rata-rata 7,27 meter. Pada kemiringan jalan (grade) didapat nilai sebesar 0% - 21,22% dalam kondisi teoritis. Setelah dilakukan perbaikan geometri jalan tambang didapat nilai produksi alat angkut sebesar 16,929,12 BCM/bulan. Dengan nilai tersebut produksi akan meningkat, sehingga target produksi yang diinginkan oleh perusahaan tercapai. Kata Kunci: AASHTO, Waktu Edar, Geometri Jalan, Produksi.